The Lodge that Beaver Built - Sonenshine, Randi, 1968-; Hunter, Anne (Somerville, Massachusetts : Candlewick Press, 2022)
"Resourceful Beaver and his family work every day to build the perfect lodge in the pond, made of branches from the shore willow and silty mud from the streambed, in a book that introduces the engineering feat of dam-building and the life cycle of beaver families"--Provided by publisher.
Keywords: Beavers -- Juvenile fiction; Beavers -- Habitations; Juvenile fiction; Beavers -- Life cycles; Juvenile fiction; Beavers -- Fiction; Beavers -- Habitations; Fiction; Beavers -- Life cycles; Fiction; Animal fiction; Stories in rhyme; Picture books